[Laiškas] / Roškovskis (Roszkowski) Bartolomejus - Juzefui Belinskiui. - (:unkn) unknown (My University, 1905)
1 laiškas apie Jadvygos Korzonovos vardo stipendijos įsteigimą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Bieliński, Józef, 1848-1926; Roškovskis (Roszkowski), Bartolomejus